Comparison of Long-Term Outcomes of Femtosecond Laser-Assisted Keratoplasty with Conventional Keratoplasty. Issue 3 (March 2016) - Daniel, Moritz C.; Böhringer, Daniel; Maier, Philip; Eberwein, Philipp; Birnbaum, Florian; Reinhard, Thomas
Abstract : Purpose: Astigmatism is a significant problem in penetrating keratoplasty. Lower astigmatism and better visual outcomes had been expected from laser-assisted penetrating keratoplasty, that is, from the top-hat, mushroom, or zig-zag cutting profiles. We report the long-term outcomes of 141 femtosecond laser–assisted penetrating keratoplasties retrospectively. We compare these outcomes with those of penetrating keratoplasty using the guided trephine system (GTS). Methods: In all, 141 femtosecond laser–assisted penetrating keratoplasties had been performed in 119 patients. The results were compared with those of conventional keratoplasty (n = 1254; visual and refractive outcomes, graft rejections, and graft failure). Results: Follow-up averaged 33 months. In eyes with keratoconus, the time to achieve a visual acuity of 10/20 (Snellen) was shorter in the mushroom than in the GTS group. However, there was no relevant long-term difference. Graft astigmatism was higher in the laser groups [keratometric astigmatism at the end of follow-up: −4.5 ± 4 (GTS), −5.8 ± 3.3 (top-hat), −5.9 ± 3.2 D (mushroom); P < 0.01]. In eyes with keratoconus, rates of graft rejection were highest in the mushroom group (55%). In the other groups, top-hat keratoplasty resulted in lower rates of rejection than GTS keratoplasty (31%). Conclusions: There is no significant difference in the refractive and visual outcomes after femtosecond laser–assisted penetrating keratoplasty compared with GTS keratoplasty. The benefits from the use of the femtosecond laser may be limited and should be weighed against an increased risk of immune reactions, higher surgical complexity, and higher costs.